PREWEDDING PHOTO PROCESSION AND THE ROLE OF THE FAMILY IN THEM - Aulil Amri (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2020)
In Islamic law, pre-wedding photos have not been regulated in detail. However, pre-wedding photo activities have become commonplace by the community. It becomes a problem when pre-wedding is currently done with an intimate scene, usually the prospective bride uses sexy clothes and is also not accompanied by her mahram when doing pre-wedding photos. Even though there have been many fatwas and studies on the limits of permissibility and prohibition in the pre-wedding procession.The results show that the pre-wedding procession that is carried out by the community in terms of poses, clothes, and also assistance in accordance with Islamic law, the law is permissible. However, it often happens in the community to take photos before the marriage contract with scenes as if they are legally husband and wife and the bride's family knows without prohibiting, directing, and guiding them according to Islamic teachings. In this case the role of the family is very important, we as parents must understand the basis of religious knowledge and how to instill religious values in our children since childhood is the key to this problem dilemma.